HISTOPATHOLOGY OF LIVER AND GUT OF Pangasius hypopthalmus THAT WERE FEED WITH CURCUMIN EXTRACT (Curcuma domestica) AND WERE INFECTED WITH Aeromonas hydrophila - Zulaiha '; Morina Riauwaty; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Pangasius hypopthalmus is one fish commodity that were known as commodity prospected and demand by employers to cultivate. The aimed this research was to understand the histopathological changes of liver and gut of Pangasius hypopthalmus that were feed with curcumin extract (Curcuma domestica) and were infected Aeromonas hydrophila. This research has been conducted in the Laboratory of Microtechnic of the Mathematics and Natural Sciences Faculty and Laboratory of Parasites and Disease of the Fisheries and Marine Science Faculty, Riau University Pekanbaru in Juny to October 2016. This study used five treatments, Kn: Negative control (feeding without the addition of curcumin and uninfected bacteria A. hydrophila), Kp: A positive control (feeding without the addition of curcumin and infected by bacteria A. hydrophila), P1: feed with curcumin addition of 0.3 g / kg, P2: Feed with the addition of curcumin of 0.5 g / kg, P3: feed with curcumin addition of 0.7 g / kg. observation tissue with histology studies and observed under a microscope. The results of the study showed that this structure of Pangasius hypopthalmus liver visible damage such as necrosis, haemorrhage, fatted degeneration, and hypertrophy. While the structure of Pangasius hypopthalmus gut visible damage such as haemorrhage, cell infiltration and goblet cell proliferation. The best results was P3 the addition of curcumin extract added to the feed with concentration of 0.7 g / kg of feed.Key words: Pangasius hypopthalmus, Liver, Gut, histopathology, Curcumin